ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI DESA MINANGA SATU KECAMATAN PUSOMAEN KABUPATEN MINAHASA TENGGARA - Jekris Anugrah Aling; Rine ., Kaunang; Mex L. Sondakh (Sam Ratulangi University, 2021)
This research aims to analyze the income of lowland rice farmers in Minanga Satu Village, Pusomaen District, Southeast Minahasa Regency. The research was conducted from January to February 2021. The types of data used in this study were primary data and secondary data which were analyzed descriptively. The results showed that the income of lowland rice farmers in Minanga Satu Village was more than eight million rupiah per hectare per one planting season. This result is obtained from the difference between the total production cost and farm income where the total production cost is Rp.9,811,832 per hectare per planting season with the farmer's income of Rp.18,189,300 per hectare per planting season, so the income is Rp.8,377,468 per hectare per growing season. Based on the results of this study, it can be seen that the income of lowland rice farming in Minanga Satu Village, Pusomaen District, Southeast Minahasa Regency if calculated per month for lowland rice farming in Minanga Satu Village, the average income is Rp. 1,396,244. This amount is small when compared to the regional minimum wage in Southeast Minahasa Regency which is more than three million rupiah.